The Effect of Diclofenac Sodium on Callus Formation in White Male Rat (Rattus norvegicus) Cruris Fracture Healing - Wibowo, Herry; Widiyanti, Prihartini (Folia Medica Indonesiana, 2022)
Highlights: • Sodium diclofenac is one of NSAID a common treatment to relieve pain associated with bone fractures. • Sodium diclofenac with a some dose of body weight could decrease the callus quality on fracture healing. Abstract: Non-steroidal anti-inflammatory drugs (NSAIDs), such as diclofenac sodium, are standard treatments to relieve pain associated with bone fractures. The bone healing process consists of four stages: inflammation, soft callus formation, complex callus formation, and bone remodeling. Previous studies mentioned that intake of NSAIDs (sodium diclofenac) could inhibit the bone healing process. This study examined the effect of diclofenac sodium intake on callus formation in fracture healing. In this study, thirty-six rats (Rattus Norvegicus) with fractures were used and divided into two groups, namely 18 rats for the control and 18 rats for the treatment group. In the treatment group, each rat was given 1.8 mg sodium diclofenac/150 grams of body weight per day. In the control group, each rat was given CMC-Na 0.5% with equal volume as diclofenac sodium in the treatment group. After 28 days, all the rats were stunned until dead, and the diameter and strength of their calluses were measured. In the treatment group with diclofenac sodium1.8 mg/ 150 grams BW/ 28 days after the tibia bone callus was pressed using the Shimadzu tool, the lowest callus strength was found to be 56.500 N, and the highest callus strength was 59.000 N. The lowest callus diameter in the treatment group was 4 mm, the highest was 5 mm. In the control group, the lowest callus strength was 76 N, and the highest callus strength was 77 N. The lowest callus diameter in the control group was 6 mm, and the highest was 8 mm. The strongest callus in the treatment group was found in the sixth observation, with a value of 59 N and a diameter of 4 mm. In the control group, the highest callus strength was 77 N, with a diameter of 7-8 mm. These measurements were found on the 5th, 7th, 8th, 9th, 16th, and 17th observations. Diclofenac sodium with a dose of 1.8 mg/150 grams of body weight could decrease the callus quality parameters, such as callus strength and diameter on fracture healing.